Peptic Ulcer-related Stenosis - Cheol Woong Choi (Yong Chan Lee, 2019)
Peptic ulcer disease involves breakdown of the epithelial lining of the stomach or duodenum. Stenosis and associated gastric outlet obstruction is the least frequent complication of peptic ulcer disease. Most cases of stenosis occur because of duodenal or pyloric cannel ulceration. Although etiologies of peptic ulcer disease and the affected patient populations have changed, the most common etiologic factors remain Helicobacter pylori infection and use of non-steroidal anti-inflammatory drugs. In recent years, eradication of H. pylori and the use of proton pump inhibitors have reduced the incidence of complications. Because the predominant cause of gastric outlet obstruction has increasingly been attributed to malignant cancer in recent years, endoscopic examination is important to differentiate benign peptic stenosis from malignant stenosis. Medical treatment such as acid-reducing drugs or H. pylori eradication is the mainstay of treatment. Endoscopic dilation or surgical management may be considered in cases of refractory or recurrent stenosis despite medical treatment. Among the major complications of peptic ulcer disease, this report will provide an overview of peptic ulcer-related stenosis.